2017
DOI: 10.1002/joc.4966
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term analysis of the asynchronicity between temperature and precipitation maxima in the United States Great Plains

Abstract: Agriculture is a critical industry to the economy of the Great Plains (GP) region of North America and sensitive to change in weather and climate. Thus, improved knowledge of meteorological and climatological conditions during the growing season and associated variability across spatial and temporal scales is important. A distinct climate feature in the GP is the asynchronicity (AS) between the timing of temperature and precipitation maxima. This study investigated a long-term observational data set to quantif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 65 publications
1
7
0
Order By: Relevance
“…The response of vegetation to climate change is the focus of many studies, especially for areas prone to drought and the associated moisture deficit, where warming and stable or even decreasing precipitation can lead to an increase in the frequency and severity of droughts [1][2][3]. The most at risk are regions where the rate of temperature increase exceeds global trends (e.g., temperate latitudes in continental Asia-Central Asia, Mongolia, North China, and South Siberia) [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The response of vegetation to climate change is the focus of many studies, especially for areas prone to drought and the associated moisture deficit, where warming and stable or even decreasing precipitation can lead to an increase in the frequency and severity of droughts [1][2][3]. The most at risk are regions where the rate of temperature increase exceeds global trends (e.g., temperate latitudes in continental Asia-Central Asia, Mongolia, North China, and South Siberia) [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Climate histories in grassland ecosystems are often variable compared to other biomes (Zhang et al 2010 ; Knapp et al 2015 ; Flanagan et al 2017 ). Our data illustrated that the pattern of variation in response to wet/dry years was not uniform across locations and these responses to interannual climate had a larger effect than responses to cattle grazing.…”
Section: Discussionmentioning
confidence: 99%
“…For the grasslands in the Great Plains, the east-west precipitation gradient results in three distinct grassland types: tallgrass prairie from Illinois to Kansas, associated with a region where rainfall amounts exceed evaporation losses, shortgrass steppe in the west limited by rainfall and growing season temperatures, and the mixed-grass prairie in the central potion as a transition between the wetter and drier prairies (Maricle and Adler 2011;Olsen et al 2013;Maricle et al 2017). Across all three grassland types, long-term precipitation and temperature is more variable compared to other biomes, often creating yearly and seasonally contrasting growing conditions (Zhang et al 2010;Knapp et al 2015;Flanagan et al 2017). For example, Flanagan et al (2017) analyzed long-term precipitation and temperature records and found a rise in asynchrony in climate maxima in the Great Plains, which results in a widening disparity between abiotic patterns and plant phenology.…”
Section: Discussionmentioning
confidence: 99%
“…Across all three grassland types, long-term precipitation and temperature is more variable compared to other biomes, often creating yearly and seasonally contrasting growing conditions (Zhang et al 2010;Knapp et al 2015;Flanagan et al 2017). For example, Flanagan et al (2017) analyzed long-term precipitation and temperature records and found a rise in asynchrony in climate maxima in the Great Plains, which results in a widening disparity between abiotic patterns and plant phenology. Here, our results emphasize the large differences in physiological and anatomical responses that can exist within a widespread C 4 grass species (A. gerardii) across multiple years and locations with distinct climate histories (contrasting precipitation and temperature) (Fig.…”
Section: Discussionmentioning
confidence: 99%